Democracy at a TTIP'ing point: Seizing a slim chance to reassert democratic sovereignty in Europe. Issue 3 (December 2014) - Crouch, Colin
<x xml:space="preserve">Abstract</x> Colin Crouch, who first diagnosed and described our 'post‐democratic' malaise a decade ago, assesses the strength of recent democratic interventions in the previously closed‐shop TTIP negotiations as a reaction to deepening crises of popular mistrust and political capture in European and western democratic national polities.